Integration of observation points for monitoring groundwater and the geochemical state of landscapes - N. G. Lyuta (Мінеральні ресурси України, 2025)
The article discusses the state of groundwater monitoring and monitoring of geochemical state of landscapes in Ukraine. According to the Procedure for Monitoring the Geological Environment (GE), these types of research are its components and should be carried out by the State Service of Geology and Mineral Resources and enterprises under its management. Groundwater monitoring is a traditional activity of the State Service of Geology and Mineral Resources, which began in the 1950s. However, the observation network is currently destroyed as a result of the war and long-term underfunding. Groundwater monitoring should be resumed on the basis of new methodological documents adapted to the EU methodological framework. Monitoring of the geochemical state of landscapes has not yet been fully launched. The organization of these two components of monitoring should be mutually coordinated, taking into account their common components and the dependence of the chemical state of groundwater on adjacent components of the GE and landscapes – soils, bottom sediments, rocks of the aeration zone. In the monitoring process, for each groundwater body, environmental objectives to be achieved within a certain period of time are set and specific measures are planned. In order for the objectives to be realistic and the measures to be effective, it is necessary to establish the origin of pollutants dissolved in the water, the content of which exceeds the criterion values. The article assesses the contribution of precipitation and soils to the formation of the chemical composition of natural waters. The necessity of integrating the monitoring of the geochemical state of landscapes sites and observation wells for groundwater monitoring is substantiated. This will make it possible to reasonably refine the list of monitored components, determine the risks of failure to achieve the environmental objectives set for groundwater bodies, establish the origin of hydrogeochemical anomalies, and plan realistic measures to improve groundwater status.